Boomerang effect of incentive reminders during shopping trips - Kulkarni, Atul; Wang, Xin Cindy; Yuan, Hong (Journal of Consumer Marketing, 2019)
Purpose This paper aims to examine the unintended negative effect of incentivizing shoppers to make unplanned purchases through incentive reminders during shopping trips. Design/methodology/approach Two experimental studies with between-subject designs were conducted to examine the effect of incentive reminders and related factors on abandonment intention. Findings When the search for unplanned purchases needed to reach promotional threshold fails, shoppers’ propensity to abandon a transaction increases if they are reminded of an incentive during their shopping trip. When the size of the planned purchases is relatively larger than the incentivized unplanned purchases, abandonment propensity is higher in response to reward type incentives, whereas when the size of the planned purchases is relatively smaller than the incentivized unplanned purchases, abandonment propensity is higher in response to avoidance type incentives. Research limitations/implications This research intersects and integrates several research domains, specifically transaction abandonment, promotional reactance, unplanned purchases and promotion framing. Practical implications Findings from this research help managers understand the possible negative consequences of incentive reminders and offer suggestions for decreasing shopper propensities to abandon transactions in response to incentive reminders aimed at increasing transaction sizes. Originality/value This is the first study to highlight (i) the possible effect of incentive reminders on transaction abandonment; (ii) the influence of the size of unplanned purchases and incentive types on abandonment; and (iii) the underlying roles of perceived value of planned purchases and fairness perceptions in abandonment.
Keywords: Incentive reminders; Promotional reactance; Transaction abandonment; dept.mrk; peer-reviewed